2016
DOI: 10.1177/0300060516650075
|View full text |Cite
|
Sign up to set email alerts
|

People with low serum folate levels have higher risk of colorectal adenoma/advanced colorectal adenoma occurrence and recurrence in China

Abstract: ObjectiveTo investigate the potential association between serum folate levels and colorectal adenoma (CRA) occurrence and recurrence.MethodsThis prospective study measured baseline serum folate levels in outpatients who were screened for CRA using colonoscopy. Participants were then randomly selected to produce one group with CRA and one without CRA. These two subgroups underwent further follow-up observations of colonoscopy to determine the occurrence of new and recurrent CRA.ResultsA total of 1310 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…34 Similarly, randomized clinical trials have shown both increased rates of cancer, lesions, and colorectal adenomas, 13 but others have found protective effects. 14,35 Our current data suggest that the therapeutic window of increased dietary folate in INS-GAS mice is earlier than 16 WPI. Furthermore, increased dietary folate intake combined with antibiotics provided no synergistic protection in H. pylori-infected INS-GAS mice at 18 WPI.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…34 Similarly, randomized clinical trials have shown both increased rates of cancer, lesions, and colorectal adenomas, 13 but others have found protective effects. 14,35 Our current data suggest that the therapeutic window of increased dietary folate in INS-GAS mice is earlier than 16 WPI. Furthermore, increased dietary folate intake combined with antibiotics provided no synergistic protection in H. pylori-infected INS-GAS mice at 18 WPI.…”
Section: Discussionmentioning
confidence: 78%
“…11,12 Randomized clinical trials have not been able to conclusively determine the effect of dietary folate in cancer. 13,14 Hypergastrinemic INS-GAS mice develop gastric cancer spontaneously by 20 months of age, but cancer can be observed as early as 24 weeks post-infection (WPI) when mice, particularly males, are infected with gastric Helicobacter spp. 15,16 We previously demonstrated that antibiotic therapy eradicated H. pylori and decreased gastric dysplasia in male INS-GAS mice, even when treatment was initiated at 22 WPI.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Consequently, three cross-sectional [ 32 33 34 ], three case-control [ 22 25 35 ], and four clinical trial studies [ 12 18 19 20 ] plus our study were included in the present meta-analysis. Among these four trial studies, the major endpoint of three of the trials was recurrent colorectal adenomas [ 12 18 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the Aspirin/Folate Polyp Prevention study (AFPPS) [ 12 ]stated that 1 mg/day supplementation of folate for 6years was associated with 67% increased risk of CRA recurrence. In Ding, Hui et al study, higher plasma folate concentrations were associated with decreased CRA occurrence and recurrence [ 29 ].In 2011, a combined analysis of the AFPPS, NHS-HPFS, & ukCAP studies was performed and determined no effect of folate supplementation on CRA recurrence [ 30 ]. In 2013, a meta-analysis of the mentioned studies found a borderline increased risk of CRA recurrence [ 31 ].This can be explained by the presence of pre-existing undiagnosed neoplastic foci [ 32 ] or can be attributed to genotype variations of folate metabolism as a significant decrease in CRC recurrence was found among patients heterozygous for MTRR A66G and MTHFR A1298C polymorphisms.…”
Section: Discussionmentioning
confidence: 99%